Anti-freezing potato modified starch as well as preparation method and application thereof
By adding stachyose to potato starch and using extrusion puffing technology to form a tight V-shaped complex, the problem of poor freeze-thaw stability of potato starch is solved, and the freeze resistance and sensory characteristics of fresh dumpling wrappers are improved.
Patent Information
- Application Number
- CN202511449331.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-12-09
AI Technical Summary
Potato starch is prone to forming small and stable ice crystals during freezing, resulting in poor freeze-thaw stability and affecting the quality and sensory characteristics of quick-frozen dumpling wrappers.
By adding stachyose to potato starch and using extrusion puffing technology, a tight V-shaped complex is formed, which enhances the glass transition temperature and network structure of the starch and inhibits ice crystal growth and recrystallization.
It significantly improves the freeze-thaw stability of potato starch, enhances the antifreeze properties and sensory characteristics of fresh dumpling wrappers, reduces water separation rate, increases solubility and swelling, and strengthens hardness, elasticity and viscosity.
Smart Images

Figure CN121086090A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of starch chemical industry, and particularly relates to an anti-freezing potato modified starch, a preparation method and application thereof. BACKGROUND
[0002] Potato starch is a high-purity starch extracted from potatoes, mainly composed of amylose and amylopectin. It has good gelatinization performance, high transparency and strong viscosity, and is widely used in the food industry as a thickening agent, stabilizer and gelling agent. However, due to the high content of amylopectin and the rich short-chain branches, these short chains are prone to recrystallization during freezing, forming fine and stable ice crystals, which are difficult to restore the original structure after thawing, resulting in water separation and gel network destruction, thereby affecting the freeze-thaw stability.
[0003] Dumplings are rich in nutrients, delicious in taste, and one of the most popular foods in China. With the cross-regional exchange of global food culture, dumplings, as a traditional Chinese food, are loved by people all over the world and are included in traditional holiday foods in many countries, and at the same time, as a convenient frozen instant product, they are widely circulated. However, long-term frozen storage and external temperature changes can cause cracking, browning and quality degradation of the frozen dumpling skin during freezing, hindering the development of the frozen dumpling skin industry. SUMMARY
[0004] The first purpose of the present application is to provide an anti-freezing potato modified starch for improving the freeze-thaw stability of potato starch, which can improve the anti-freezing performance and sensory characteristics of fresh dumpling skin. The second purpose of the present application is to provide a preparation method of the anti-freezing potato modified starch. The third purpose of the present application is to provide the application of the anti-freezing potato modified starch.
[0005] The preparation method of the anti-freezing potato modified starch comprises the following steps: adding stachyose to potato starch, mixing, adjusting the moisture content by adding water, and then performing extrusion treatment with an extrusion puffing machine, and finally drying and crushing to obtain the anti-freezing potato modified starch.
[0006] Preferably, the addition amount of stachyose is 1-3% of the mass of potato starch. Stachyose can increase the glass transition temperature of the system, so that the system enters the glass state faster during freezing, thereby inhibiting the growth and recrystallization of ice crystals. In addition, the molecular size and structure of stachyose are very suitable for embedding into the helical cavity of amylose, forming a more stable and compact V-shaped complex.
[0007] Preferably, the extrusion temperature is 50~90℃, and the frequency of the puffing machine is 20~30Hz. Different extrusion temperatures result in different degrees of starch gelatinization. At low extrusion temperatures, the starch is in a partially gelatinized state, and amylose can undergo orderly entanglement and complexation with stachyose molecules to form a tightly structured V-shaped complex. Furthermore, low extrusion temperatures can preserve the network framework, and amylopectin is not completely melted. Its original branched structure can serve as a natural framework for the gel network, forming a stable, multi-scale network. On the other hand, high extrusion temperatures will cause the starch granules to completely melt, the crystal structure to be completely destroyed, the molecular chains to be overextended or even degraded, the system viscosity to be too low, the fluidity to be too strong, and the gel network to be fragile. During freezing, it is easily pierced by ice crystals, and severe water separation will occur after thawing. At different extruder frequencies, the effect of shear force varies. At low frequencies, the material stays in the barrel for a longer time, allowing more time for heat exchange and molecular interaction. However, the shear force is relatively small, which may result in insufficient gelatinization or mixing. At high frequencies, strong shear force can efficiently break down starch granules, promoting the extension and mixing of molecular chains. However, the rapid passage of material through the extruder may lead to insufficient reaction time. Furthermore, high shear generates a large amount of frictional heat, causing the actual temperature of the material to rise and thus deviating the system from the preset optimal temperature conditions.
[0008] Preferably, the moisture content is 40-50%.
[0009] Preferably, the drying temperature is 40°C, and the drying process is carried out until the moisture content is ≤14%.
[0010] The antifreeze modified potato starch prepared by the preparation method described in this invention.
[0011] Preferably, the water separation rate of the antifreeze modified potato starch after 5 freezing cycles is 62.61~74.93%.
[0012] Preferably, the resistant potato modified starch has a solubility of 17.32-21.85%, an expansion of 15.37-18.85%, and a resistant starch content of 40.42-55.28% after being frozen 5 times.
[0013] The application of the antifreeze modified potato starch described in this invention in frozen food processing.
[0014] Preferably, the frozen food is dumpling wrappers.
[0015] Preparation of fresh dumpling wrappers with added antifreeze potato starch: Antifreeze potato modified starch is added to wheat flour, mixed, and then 30% water is added and stirred to obtain dough flakes; the dough is allowed to mature and rise, rolled into sheets, matured and risen again, rolled in reverse direction, and cut into fresh dumpling wrappers.
[0016] Preferably, the amount of antifreeze modified potato starch added to the dumpling wrapper is 3-7% of the mass of wheat flour.
[0017] Preferably, after being frozen five times, the dumpling wrappers have a moisture content of 22.11-24.65%, a freezeable water content of 28.23-30.04%, a brightness of 79.96-83.03, a red-green hue of 0.05-0.14, a yellow-blue hue of 16.25-18.12, and a hardness of 25.33-26.93 N / cm². 2 Its elasticity is 0.72~0.75mm, and its chewiness is 24.92~26.14 N / cm. 2 The viscosity is 25.04 ~ 26.59 N / cm. 2 .
[0018] Invention Mechanism:
[0019] In this invention, the freeze-thaw stability of potato starch is improved by adding stachyose and combining it with extrusion technology. This invention uses extrusion technology to prepare freeze-resistant modified potato starch. Under the low-temperature extrusion and high shear force of the extruder, the potato starch granules are partially gelatinized and physically broken down, disrupting the crystalline regions of natural starch and reducing the driving force for subsequent retrogradation. Furthermore, the strong shear force causes controlled breakage of starch molecules, generating more short-chain fragments. These fragments rearrange under the high pressure and shear field within the extrusion chamber, forming a denser and more uniform amorphous network, significantly improving water retention and freeze-thaw stability. The dissolution and molecular degradation of amylose further increase solubility. Stachyose is a natural functional oligosaccharide with good thermal stability and solubility. As a prebiotic, it is not broken down by digestive enzymes and its metabolism does not depend on insulin. It helps regulate the intestinal flora, promotes intestinal health, and helps lower blood pressure and blood lipids. Its cyclic structure contains 8 free hydroxyl groups, which are highly hydrophilic and can effectively enhance the ability of starch systems to bind free water, reduce ice crystal formation and recrystallization, inhibit enzymatic hydrolysis, and reduce starch digestibility.
[0020] The synergistic effect of antifreeze modified potato starch and gluten network enhances the density of dumpling wrapper structure, improves moisture distribution, and slows down moisture migration and browning reactions during frozen storage. After multiple freeze-thaw cycles, dumpling wrappers with the added antifreeze modified potato starch of this invention exhibit superior hardness, elasticity, chewiness, and stickiness compared to those without, significantly improving the texture and sensory quality of fresh dumpling wrappers.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The antifreeze modified potato starch of the present invention uses extrusion treatment of potato starch and stachyose to improve the freeze-thaw stability of potato starch, overcoming the problems of high water separation rate, insufficient solubility and swelling, and low digestibility of natural potato starch; (2) The water separation rate of the antifreeze modified potato starch of the present invention after 5 freezes is 62.61~74.93%, which is 11.23~2% lower than that of untreated potato starch. 5.83%; (3) The solubility and swelling degree of the antifreeze modified potato starch of the present invention are 17.32~21.85% and 15.37~18.85%, respectively, which are 235.22~552.24% and 34.59~65.06% higher than those of untreated potato starch; (4) The resistant starch content of the antifreeze modified potato starch is 40.42~55.28%, which is 21.02~65.51% higher than that of untreated potato starch; (5) The preparation method is simple; (6) The antifreeze modified potato starch of the present invention is applied to fresh dumpling wrappers, which improves the antifreeze performance and sensory characteristics of the dumpling wrappers. After 5 freeze-thaw cycles, the moisture content of the fresh dumpling wrappers is 22.11~24.65%, which is 11.16~23.93% higher than that of fresh dumpling wrappers without the addition; the freezeable water content of the fresh dumpling wrappers is 28.23~30.04%, which is 10.41~15.83% lower than that of fresh dumpling wrappers without the addition; The brightness and red-green saturation of the fresh dumpling skin were 79.96-83.03 and 0.05-0.14, respectively, which were increased by 11.69-15.98% and 18.05-144.44% compared with the unadded fresh dumpling skin; the yellow-blue saturation of the fresh dumpling skin was 16.25-18.12, which was decreased by 7.52-15.76% compared with the unadded fresh dumpling skin; the hardness, elasticity, chewiness, and stickiness of the fresh dumpling skin were 25.33-26.93 N / cm. 2 , 0.72~0.75mm, 24.92~26.14 N / cm 2 and 25.04~26.59 N / cm 2 Compared with fresh dumpling wrappers without additives, the percentages increased by 32.34~40.70%, 4.35~8.70%, 59.44~67.24%, and 33.90~42.19%, respectively. Attached Figure Description
[0022] Figure 1 The images show the morphology of the modified starch gels of antifreeze potatoes in Examples 3-9 and Comparative Examples 1-2 under different freeze-thaw cycles. Detailed Implementation
[0023] The technical solution of the present invention will be further described below with reference to the embodiments.
[0024] Example 1
[0025] The antifreeze modified potato starch of the present invention is prepared by means of the following steps:
[0026] Take potato starch, add 1% stachyose by weight of potato starch and mix well. Adjust the moisture content to 40%. Process it with an extrusion puffing machine at an extrusion temperature of 60℃ and a main machine frequency of 25 Hz. Then dry it at 40℃ until the moisture content is ≤14% and pulverize it to 100 mesh to obtain antifreeze modified potato starch.
[0027] Application: By adding antifreeze modified potato starch to the preparation of fresh dumpling wrappers, the effects of this addition on the quality (moisture content, freezeable water, color, and other properties) of the fresh dumpling wrappers under freeze-thaw conditions were evaluated.
[0028] The preparation process of fresh dumpling wrappers with added antifreeze modified potato starch is as follows: 3% (w / w) antifreeze modified potato starch is added to wheat flour, mixed, and then 30% water by weight of flour is added and stirred to obtain dough flakes; the dough is matured and proofed, rolled into sheets, matured and proofed again, rolled in reverse direction, and cut into fresh dumpling wrappers.
[0029] Example 2
[0030] The antifreeze modified potato starch of the present invention is prepared by means of the following steps:
[0031] Take potato starch, add 2% stachyose by weight of potato starch and mix well. Adjust the moisture content to 40%. Process it with an extrusion puffing machine at an extrusion temperature of 60℃ and a main machine frequency of 25Hz. Then dry it at 40℃ until the moisture content is ≤14% and pulverize it to 100 mesh to obtain antifreeze modified potato starch.
[0032] Application: By adding antifreeze modified potato starch to the preparation of fresh dumpling wrappers, the effects of this addition on the quality (moisture content, freezeable water, color, and other properties) of the fresh dumpling wrappers under freeze-thaw conditions were evaluated.
[0033] The preparation process of fresh dumpling wrappers with added antifreeze modified potato starch is as follows: 5% (w / w) antifreeze modified potato starch is added to wheat flour, mixed, and then 30% water by weight of flour is added and stirred to obtain dough flakes; the dough is allowed to mature and rise, rolled into sheets, matured and risen again, rolled in reverse direction, and cut into fresh dumpling wrappers.
[0034] Example 3
[0035] The antifreeze modified potato starch of the present invention is prepared by means of the following steps:
[0036] Take potato starch, add 3% stachyose by weight of potato starch and mix well. Adjust the moisture content to 40%. Process it with an extrusion puffing machine at an extrusion temperature of 60℃ and a main machine frequency of 25 Hz. Then dry it at 40℃ until the moisture content is ≤14% and pulverize it to 100 mesh to obtain antifreeze modified potato starch ES-60.
[0037] Application: By adding antifreeze modified potato starch to the preparation of fresh dumpling wrappers, the effects of this addition on the quality (moisture content, freezeable water, color, and other properties) of the fresh dumpling wrappers under freeze-thaw conditions were evaluated.
[0038] The preparation process of fresh dumpling wrappers with added antifreeze potato modified starch is as follows: 7% (w / w) antifreeze potato modified starch is added to wheat flour, mixed, and then 30% water by weight of flour is added and stirred to obtain dough flakes; the dough is matured and proofed, rolled into sheets, matured and proofed again, rolled in reverse direction, and cut into fresh dumpling wrappers.
[0039] Example 4
[0040] Based on Example 2, the extrusion temperature was changed to 50°C while keeping other conditions unchanged to obtain antifreeze modified potato starch ES-50.
[0041] Example 5
[0042] Based on Example 2, the extrusion temperature was changed to 70°C, while other conditions remained unchanged, to obtain frost-resistant modified potato starch ES-70.
[0043] Example 6
[0044] Based on Example 2, the extrusion temperature was changed to 80°C while keeping other conditions unchanged to obtain frost-resistant modified potato starch ES-80.
[0045] Example 7
[0046] Based on Example 2, the extrusion temperature was changed to 90°C while keeping other conditions unchanged to obtain frost-resistant modified potato starch ES-90.
[0047] Example 8
[0048] Based on Example 2, the extrusion temperature was changed to 60°C, the extrusion host frequency was changed to 20 Hz, and the other conditions remained unchanged to obtain antifreeze modified potato starch ES-20Hz.
[0049] Example 9
[0050] Based on Example 2, the extrusion temperature was changed to 60°C, the extrusion host frequency was changed to 30 Hz, and the other conditions remained unchanged to obtain antifreeze modified potato starch ES-30Hz.
[0051] Comparative Example 1
[0052] Unprocessed potato starch (Control).
[0053] Comparative Example 2
[0054] Take potato starch, adjust the moisture content to 40%, process it with an extrusion puffing machine at an extrusion temperature of 60℃ and a main machine frequency of 25 Hz, then dry it at 40℃ until the moisture content is ≤14%, and pulverize it to 100 mesh to obtain modified potato starch EP.
[0055] 1. Determination of water separation volume
[0056] ① Preparation of starch paste: Add 0.5 g of the starch to be tested to a 50 ml beaker, add 5 ml of deionized water, and stir well. Then heat the starch solution at 90℃ with continuous stirring for 30 seconds to form a paste.
[0057] ② Cool the starch paste (10%, w / v), transfer the paste to centrifuge tubes, freeze at -18°C for 24 hours, then thaw at room temperature, followed by centrifugation at 4000 rpm for 10 minutes. The first freeze-thaw cycle refers to the above procedure, while subsequent cycles (2nd to 5th) are calculated using the same method, with the water separation rate of the starch paste calculated according to the following formula:
[0058]
[0059] In the formula: m1 is the weight of the centrifuge tube (g), m2 is the total weight of the centrifuge tube and the paste before freezing (g), and m3 is the weight of the sediment (g).
[0060] The test results of Examples 1-9 and Comparative Examples 1-2 are shown in Table 1 and 2. Figure 1 As shown.
[0061] Table 1. Water separation rate (%) of modified starch from freeze-resistant potatoes
[0062]
[0063] Table 1 shows that the modified potato starches in Examples 1-9 exhibited good freeze-thaw resistance. Compared with Comparative Examples 1 and 2, they significantly reduced water exudation. This is attributed to the cross-linking of potato starch with stachyose under extrusion, forming a random network structure that facilitates the binding of water molecules. In Example 1, the water exudation rate of the freeze-thaw resistant potato starch with 1% stachyose addition after 5 freeze-thaw cycles was 11.57% lower than that of Comparative Example 1 and 1.13% lower than that of Comparative Example 2. In Example 2, the water exudation rate of the freeze-thaw resistant potato starch with 2% stachyose addition after 5 freeze-thaw cycles was 25.83% lower than that of Comparative Example 1 and 17.06% lower than that of Comparative Example 2. In Example 3, the water exudation rate of the freeze-thaw resistant potato starch with 3% stachyose addition after 5 freeze-thaw cycles was 12.32% lower than that of Comparative Example 1 and 1.96% lower than that of Comparative Example 2. In Example 4, the water exudation rate of the freeze-thaw resistant potato starch with an extrusion temperature of 50℃ after 5 freeze-thaw cycles was significantly lower than that of Comparative Example 1. Example 1 showed a 12.40% reduction compared to Comparative Example 2, while Comparative Example 2 showed a 2.05% reduction. In Example 5, the water separation rate of the antifreeze potato starch with an extrusion temperature of 70°C after 5 freeze-thaw cycles was 22.63% lower than Comparative Example 1 and 13.49% lower than Comparative Example 2. In Example 6, the water separation rate of the antifreeze potato starch with an extrusion temperature of 80°C after 5 freeze-thaw cycles was 17.85% lower than Comparative Example 1 and 8.15% lower than Comparative Example 2. In Example 7, the water separation rate of the antifreeze potato starch with an extrusion temperature of 90°C after 5 freeze-thaw cycles was lower than Comparative Example 1. The water separation rate of the antifreeze potato starch after 5 freeze-thaw cycles was reduced by 16.51% compared to Comparative Example 1 (6.65% reduction in Comparative Example 2). In Example 8, the water separation rate of the antifreeze potato starch after 5 freeze-thaw cycles with a main extrusion frequency of 20Hz was reduced by 11.23% compared to Comparative Example 1 and by 0.74% compared to Comparative Example 2. In Example 9, the water separation rate of the antifreeze potato starch after 5 freeze-thaw cycles with a main extrusion frequency of 30Hz was reduced by 22.12% compared to Comparative Example 1 and by 12.92% compared to Comparative Example 2. In Examples 1-3, the water separation rate of the antifreeze potato starch after 5 freeze-thaw cycles showed a trend of first decreasing and then increasing with increasing stachyose content. The water separation rate was lowest and the freeze-thaw stability was best when the stachyose content was 2%. In Examples 2 and 4-7, the water separation rate of the antifreeze potato starch after 5 freeze-thaw cycles first decreased and then increased with increasing extrusion temperature. The freeze-thaw stability was optimal when the extrusion temperature was 70℃. In Examples 2 and 8-9, as the extrusion host frequency increases, the water separation of the antifreeze potato starch after 5 freeze-thaw cycles first decreases and then increases. Therefore, the freeze-thaw stability is optimal when the host frequency is 25 Hz.
[0064] 2. Determination of solubility and swelling
[0065] Test method: Weigh the centrifuge tube (m0). Dissolve 0.2 g of starch (m1) in 10 mL of distilled water. Let stand for 5 min. Vortex for 20 s before placing the solution in a water bath. Heat the solution in a 90°C water bath for 30 min, mixing with shaking. After cooling to room temperature, place the mixture in a centrifuge and centrifuge at 3500 r for 10 min. Weigh the aluminum box (m2) and pour the supernatant into it. Record the total mass of the precipitate and centrifuge tube as m3. Heat the box containing the super-eluting solution at 105°C to constant weight. Weigh the dried aluminum box (m4). Calculate the solubility and swelling degree using the following formulas:
[0066] .
[0067]
[0068] In the formula: m0 is the mass of the centrifuge tube (g), m1 is the mass of starch (g), m2 is the mass of the empty aluminum box (g), m3 is the total mass of the sediment and centrifuge tube (g), m4 is the mass of the aluminum box after drying, and S is the solubility (%).
[0069] The test results of Examples 1-9 and Comparative Examples 1-2 are shown in Table 2.
[0070] Table 2. Solubility and swelling properties of modified starch from freeze-resistant potatoes
[0071]
[0072] Table 2 shows that the modified potato starches in Examples 1-9 exhibited good solubility, swelling capacity, and resistance to starch digestion. Compared to Comparative Example 1, the solubility and swelling capacity of the antifreeze potato starch with 1% stachyose addition in Example 1 increased by 510.75% and 49.30%, respectively; compared to Comparative Example 2, the solubility and swelling capacity increased by 92.29% and 34.68%, respectively. Compared to Comparative Example 1, the solubility and swelling capacity of the antifreeze potato starch with 2% stachyose addition in Example 2 increased by 552.24% and 65.06%, respectively; compared to Comparative Example 2, the solubility and swelling capacity increased by 31.31% and 48.89%, respectively. Compared to Comparative Example 1, the stachyose addition in Example 3 was 3%. The solubility and swelling capacity of the antifreeze potato starch in Example 4 increased by 506.87% and 51.58%, respectively, compared to Comparative Example 2 by 22.18% and 36.73%, respectively. Compared to Comparative Example 1, the solubility and swelling capacity of the antifreeze potato starch extruded at 50°C in Example 4 increased by 490.45% and 41.68%, respectively, compared to Comparative Example 2 by 18.87% and 27.80%, respectively. Compared to Comparative Example 1, the solubility and swelling capacity of the antifreeze potato starch extruded at 70°C in Example 5 increased by 464%. Compared to Comparative Example 2, the solubility and swelling properties of the antifreeze potato starch extruded at 80°C in Example 6 increased by 13.58% and 35.15%, respectively; compared to Comparative Example 1, the solubility and swelling properties of the antifreeze potato starch extruded at 90°C in Example 7 increased by 468.06% and 35.55%, respectively; compared to Comparative Example 2, the solubility and swelling properties increased by 14.36% and 22.27%, respectively; compared to Comparative Example 1, the solubility and swelling properties of the antifreeze potato starch extruded at 90°C in Example 7 increased by 420.90% and 34.59%, respectively; compared to Comparative Example 2, the solubility and swelling properties increased by 13.58% and 35.15%, respectively. The solubility and swelling degree of the antifreeze potato starch in Example 8 with a host frequency of 20 Hz increased by 4.87% and 21.41%, respectively. Compared with Comparative Example 1, the solubility and swelling degree of the antifreeze potato starch in Example 8 with a host frequency of 20 Hz increased by 417.01% and 45.88%, respectively, and compared with Comparative Example 2, the solubility and swelling degree increased by 4.09% and 31.605%, respectively. Compared with Comparative Example 1, the solubility and swelling degree of the antifreeze potato starch in Example 9 with a host frequency of 30 Hz increased by 477.91% and 53.59%, respectively, and compared with Comparative Example 2, the solubility and swelling degree increased by 16.35% and 38.55%, respectively. In Examples 1-3, with the increase of stachyose addition, the solubility of the antifreeze potato starch first increased and then decreased, and the swelling degree also showed a trend of first increasing and then decreasing. When the stachyose addition was 2%, the solubility and swelling degree were optimal. In Examples 2 and 4-7, the solubility of antifreeze potato starch first increased and then decreased with the increase of extrusion temperature, and the swelling degree first increased and then decreased. The solubility and swelling degree were optimal when the extrusion temperature was 60°C.In Examples 2 and 8-9, as the frequency of the extrusion host increases, the solubility of antifreeze potato starch first increases and then decreases, and the expansion also shows a trend of first increasing and then decreasing. When the host frequency is 25Hz, the solubility and expansion are optimal.
[0073] 3. Determination of resistant starch content
[0074] Test Method: Add 0.2 g of the starch to be tested to a 50 mL beaker, add 8 mL of deionized water, and stir the mixture at 500 rpm for 10 min at room temperature using a magnetic stirrer to ensure better and more uniform mixing. Then, heat the starch solution at 90℃ with continuous stirring for 20 min to form a paste-like consistency, obtain starch slurry, and cool to room temperature for testing. Add 0.3 g of α-amylase (10 U / mg) to 5.0 mL of phosphate buffer (pH 5.2), stir for 10 min, add 10 μL of amylase (150,000 u / mL) to the supernatant, vortex to mix, and obtain a mixed enzyme solution of α-amylase and amylase. Add 10.0 mL of phosphate buffer (pH 5.2) to the starch slurry, stir continuously at 37℃ for 10 min, and then add 5.0 mL of the mixed enzyme solution. At 20 min and 120 min after digestion, 0.1 mL of the reaction solution was mixed with 0.9 mL of anhydrous ethanol to inactivate the enzyme. The mixture was centrifuged (4000 rpm, 10 min), and the total glucose concentration of the digested hydrolysates (G20 and G120, respectively) at 20 min and 120 min was determined using a glucose oxidase-peroxidase kit (A154-1-1, Nanjing Jiancheng Bioengineering Institute). The absorbance of the supernatant was measured at 505 nm, and the glucose content was calculated. The RDS, SDS, and RS values were calculated. The specific formulas are as follows:
[0075] RDS(%) = G20 × 0.9 × 100
[0076] SDS(%)=(G120-G20)×0.9×100
[0077] RS(%) = TS - RDS - SDS
[0078] In the formula: G20 is the glucose content (mg) in the supernatant after 20 min of enzymatic hydrolysis; G120 is the glucose content (mg) in the supernatant after 120 min of enzymatic hydrolysis; TS is the total starch content in the sample.
[0079] The test results of Examples 1-9 and Comparative Examples 1-2 are shown in Table 3.
[0080] Table 3. Resistant starch content of modified starch from frost-resistant potatoes
[0081]
[0082] Table 3 shows that after five freeze-thaw cycles, the resistant starch content of the modified potato starch in Examples 1-9 was significantly increased. Compared with Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 1 with 1% stachyose addition increased by 54.01%, and by 42.06% compared with Comparative Example 2; compared with Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 2 with 2% stachyose addition increased by 65.51%, and by 52.67% compared with Comparative Example 2; compared with Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 3 with 3% stachyose addition increased by 49.04%, and by 37.48% compared with Comparative Example 2; compared with Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 4 with an extrusion temperature of 50℃ increased by 52.85%, and by 40.96% compared with Comparative Example 2; compared with Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 5 with an extrusion temperature of 70℃ increased by 52.85%, and by 40.96% compared with Comparative Example 2. The resistant starch content increased by 40.78%, and by 29.85% compared to Comparative Example 2. Compared to Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 6, with an extrusion temperature of 80°C, increased by 28.83%, and by 18.83% compared to Comparative Example 2. Compared to Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 7, with an extrusion temperature of 90°C, increased by 21.02%, and by 11.63% compared to Comparative Example 2. Compared to Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 8, with a main motor frequency of 20Hz, increased by 46.86%, and by 35.46% compared to Comparative Example 2. Compared to Comparative Example 1, the resistant starch content of the antifreeze potato starch in Example 9, with a main motor frequency of 30Hz, increased by 39.67%, and by 28.83% compared to Comparative Example 2. In Examples 1-3, the resistant starch content of the antifreeze potato starch first increased and then decreased with the increase of stachyose addition, reaching its highest level when the stachyose addition was 2%. In Examples 2 and 4-7, the resistant starch content of the antifreeze potato starch first increased and then decreased with increasing extrusion temperature, reaching its highest level at an extrusion temperature of 60°C. In Examples 2 and 8-9, the resistant starch content of the antifreeze potato starch first increased and then decreased with increasing extrusion frequency, reaching its highest level at a frequency of 25 Hz.
[0083] 4. Determination of moisture content in fresh dumpling wrappers
[0084] Refer to GB 5009.3-2016 "National Food Safety Standard - Determination of Moisture in Food".
[0085] The testing method is as follows:
[0086] ① Take a clean aluminum flat weighing bottle, place it in a drying oven at 101℃~105℃, with the bottle cap tilted against the side of the bottle, heat for 1 hour, take it out and cover it, place it in a desiccator to cool for 0.5 hours, weigh it, and repeat the drying process until the difference between the two weighings does not exceed 2 mg, which is constant weight.
[0087] ② Grind the dumpling wrappers until the particles are less than 2 mm, weigh 2 g of the sample (accurate to 0.0001 g), and put it into this weighing bottle;
[0088] ③ Place in a drying oven at 101℃~105℃ and dry for 2 hours;
[0089] ④ After cooling in the desiccator for 0.5 hours, weigh the sample. Then, place it in a drying oven at 101℃~105℃ for approximately 1 hour. After removing it, cool it in the desiccator for 0.5 hours and weigh it again. Repeat the above steps until the difference between the two weighings does not exceed 2 mg, which is considered constant weight. The moisture content of the sample is calculated using the following formula:
[0090] .
[0091] In the formula: X is the moisture content in the sample, in grams per 100 grams (g / 100g); m1 is the mass of the weighing bottle and the sample, in grams (g); m 2为 : The mass of the weighing bottle and the sample after drying, in grams (g); m3 is the mass of the weighing bottle, in grams (g); 100 is the place conversion factor.
[0092] The test results are shown in Tables 4-6 (the control group consisted of untreated potato starch with the same amount of modified starch as antifreeze potato starch).
[0093] Table 4. Moisture content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 1 during freeze-thaw process.
[0094]
[0095] As shown in Table 4, the addition of freeze-resistant modified potato starch resulted in good freeze-thaw stability of the dumpling wrappers. After five freeze-thaw cycles, the moisture content remained at 23.24%, which was 16.84% higher than that of the control group. The freeze-resistant modified potato starch can better bind to the gluten protein network, thus strengthening the binding of water molecules.
[0096] Table 5. Moisture content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 2 during freeze-thaw process.
[0097]
[0098] As shown in Table 5, after five freeze-thaw cycles, the moisture content of the dumpling wrappers with added antifreeze starch was 24.65%, which was 23.93% higher than that of the control group.
[0099] Table 6. Moisture content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 3 during freeze-thaw process.
[0100]
[0101] As shown in Table 6, after five freeze-thaw cycles, the moisture content of the dumpling wrappers with added antifreeze starch was 22.11%, which was 11.16% higher than that of the control group.
[0102] 5. Determination of the freezeable water content of fresh dumpling wrappers
[0103] The testing method is as follows:
[0104] ① Weigh about 10 mg of frozen and freeze-thawed dough sample, seal it in a small crucible and place it in the DSC sample cell, while using an empty crucible as a control.
[0105] ② The temperature program was set to equilibrate at −30 ℃ for 5 min, then increase to 15 ℃ at a rate of 10 ℃ / min. The instrument's scanning curve was recorded, and the enthalpy of ice crystal melting of the dumpling wrapper was obtained using TA Universal Analysis software. The formula for calculating the freezeable water content (Fw) of the wrapper sample is as follows:
[0106]
[0107] F w The content of freezeable water, %; ΔH w The enthalpy of melting of the dough, J; Δ fus H m =333.3 J / g; m is the mass of the dough, in g; W A The moisture content of the dough is %.
[0108] The test results are shown in Tables 7-9.
[0109] Table 7. Freezeable water content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 1 during the freeze-thaw process.
[0110]
[0111] As shown in Table 7, after five freeze-thaw cycles, the content of freezeable water was significantly reduced by adding modified potato starch. The modified potato starch adsorbed the moisture inside the fresh dumpling skin, reducing recrystallization during the freeze-thaw process.
[0112] Table 8. Freezeable water content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 2 during the freeze-thaw process.
[0113]
[0114] As shown in Table 8, after five freeze-thaw cycles, the freezeable water content of dumpling skin with added antifreeze starch was 28.23%, which was 15.83% lower than that of the control group.
[0115] Table 9. Freezeable water content (%) of fresh dumpling wrappers with added antifreeze potato modified starch in Example 3 during the freeze-thaw process.
[0116]
[0117] As shown in Table 9, after five freeze-thaw cycles, the freezeable water content of dumpling skin with added antifreeze starch was 30.05%, which was 10.41% lower than that of the control group.
[0118] 6. Method for determining the color of fresh dumpling wrappers
[0119] Test method: Dumpling wrappers under different freezing and freeze-thaw cycles were placed in a steamer and steamed for 8 minutes. Their color was measured by DigiEye electronic eye. L* is the brightness, a* is the redness, and b* is the yellowness. The center of the front and back of the wrapper was selected for testing and the mean value of the color characteristics was calculated. Each group of samples was measured 3 times.
[0120] The test results are shown in Tables 10-12.
[0121] Table 10 Effect of Antifreeze Modified Potato Starch on Color of Fresh Dumpling Wrappers during Freeze-Thaw Process (Example 1)
[0122]
[0123] As shown in Table 10, the brightness of the dumpling skin decreased more slowly than that of the control group, indicating that the modified starch of refrigerated potatoes has a certain color-preserving effect under freeze-thaw conditions.
[0124] Table 11. Effect of freeze-resistant modified potato starch on the color of fresh dumpling wrappers during freeze-thaw process in Example 2.
[0125]
[0126] As shown in Table 11, after five freeze-thaw cycles, the L* and a* values of the dumpling skin with added antifreeze starch were 83.03 and 0.08, respectively, which were 15.98% and 144.44% higher than those of the control group. The b* value of the dumpling skin with added antifreeze starch was 16.25, which was 15.76% lower than that of the control group.
[0127] Table 12. Effect of Antifreeze Modified Potato Starch on Color of Fresh Dumpling Wrappers during Freeze-Thaw Process (Example 3)
[0128]
[0129] As shown in Table 12, after five freeze-thaw cycles, the L* and a* values of the dumpling skin with added antifreeze starch were 79.96 and 0.05, respectively, which were 11.69% and 118.50% higher than those of the control group. The b* value of the dumpling skin with added antifreeze starch was 17.84, which was 7.52% lower than that of the control group.
[0130] 7. Determination of the textural properties of fresh dumpling wrappers
[0131] Test method:
[0132] ① After re-steaming dumpling wrappers from different freeze-thaw cycles in a steamer for 10 min, their texture properties were determined using an XT plus texture analyzer (XTC-18, China).
[0133] ② Using a P50 probe, place the re-steamed dough at the center of the texture analyzer base, set to TPA mode, with a pre-test speed of 2 mm / s, a mid-test speed of 0.8 mm / s, a post-test speed of 0.8 mm / s, a compression ratio of 70%, and a trigger force of 0.05 g. Perform 5 parallel tests for each sample group.
[0134] The test results are shown in Tables 13-15.
[0135] Table 13 Effect of freeze-resistant modified potato starch on the textural properties of fresh dumpling wrappers during freeze-thaw cycles, Example 1
[0136]
[0137] Table 13 shows that after five freeze-thaw cycles, the dumpling wrappers with added freeze-resistant modified potato starch exhibited significantly higher hardness, elasticity, chewiness, and stickiness than the control group's wrappers. These indicators suggest that freeze-resistant modified potato starch improves the quality of dumpling wrappers under freeze-thaw conditions.
[0138] Table 14. Effect of freeze-resistant modified potato starch on the textural properties of fresh dumpling wrappers during freeze-thaw cycles, as described in Example 2.
[0139]
[0140] Table 14 shows that after five freeze-thaw cycles, the hardness, elasticity, chewiness, and stickiness of the dumpling wrappers with added antifreeze starch were 26.93 N / cm². 2 0.75 mm, 26.14 N / cm 2 and 26.59 N / cm 2 Compared with the control group, the rates were 40.70%, 8.70%, 67.24%, and 42.19%, respectively.
[0141] Table 15 Effect of freeze-resistant modified potato starch on the textural properties of fresh dumpling wrappers during freeze-thaw cycles, as described in Example 3.
[0142]
[0143] Table 15 shows that after five freeze-thaw cycles, the hardness, elasticity, chewiness, and stickiness of the dumpling wrappers with added antifreeze starch were 25.33 N / cm. 2 0.72 mm, 24.92 N / cm 2 and 25.04 N / cm 2 Compared with the control group, the rates were 32.34%, 4.35%, 59.44%, and 33.90%, respectively.
[0144] In summary, modified starch was prepared by extruding a mixture of potato starch and stachyose. This resistant starch exhibits excellent functional properties and can improve the quality of fresh dumpling wrappers during freeze-thaw cycles, showing great potential for application in the field of frozen foods.
Claims
1. A method for preparing antifreeze modified potato starch, characterized in that, Includes the following steps: Stachyose was added to potato starch, mixed well, water was added to adjust the moisture content, and the mixture was extruded using an extruder. Finally, it was dried and pulverized to obtain frost-resistant modified potato starch.
2. The method for preparing antifreeze modified potato starch according to claim 1, characterized in that, The amount of stachyose added is 1-3% of the mass of potato starch.
3. The method for preparing antifreeze modified potato starch according to claim 1, characterized in that, The extrusion temperature is 50~90℃, and the frequency of the puffing machine is 20~30 Hz.
4. A modified potato starch resistant to freezing prepared by any one of claims 1 to 3.
5. The antifreeze modified potato starch according to claim 4, characterized in that, The water separation rate of the frost-resistant modified potato starch after 5 freezing cycles was 62.61-74.93%.
6. The antifreeze modified potato starch according to claim 4, characterized in that, The resistant potato modified starch has a solubility of 17.32-21.85%, an expansion of 15.37-18.85%, and a resistant starch content of 40.42-55.28% after being frozen 5 times.
7. The application of the antifreeze modified potato starch according to any one of claims 4 to 6 in the processing of frozen foods.
8. The application according to claim 7, characterized in that, The frozen food is dumpling wrappers.
9. The application according to claim 8, characterized in that, The amount of antifreeze modified potato starch added to the dumpling wrapper is 3-7% of the mass of wheat flour.
10. The application according to claim 8 or 9, characterized in that, After being frozen five times, the dumpling wrappers had a moisture content of 22.11–24.65%, a freezeable water content of 28.23–30.04%, a brightness of 79.96–83.03, a red-green hue of 0.05–0.14, a yellow-blue hue of 16.25–18.12, and a hardness of 25.33–26.93 N / cm². 2 Its elasticity is 0.72~0.75mm, and its chewiness is 24.92~26.14 N / cm. 2 The viscosity is 25.04 ~ 26.59 N / cm. 2 .